2019
DOI: 10.1088/1755-1315/309/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Testing of Aflatoxin by Using Image Processing and Artificial Neural Network

Abstract: Aflatoxin can be recognized clearly by using UV-light. This information is very important to develop the device for detecting the aflatoxin inside the corn by using image processing. Current research related to identification of aflatoxin has been conducted manually by the experts. This method have some weakness including subjectivity factors, inconsistent result, and time required used. Based on the problems above, it needed to create the rapid testing device for identification of aflatoxin with consistence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Moreover, it was proclaimed that AF shows bright greenish‐yellow fluorescence (BGYF) under ultraviolet (UV) light at a wavelength of 365 nm (Wicklow, 1999). Soemantri and Diyono (2019) applied this information for rapid detection of AF in corn using UV sensing digital camera with 5‐watt UV lamps. They built ANN architecture considering 10 input parameters, viz.…”
Section: Application Of Digital Color Imaging For Mold and Mycotoxins...mentioning
confidence: 99%
“…Moreover, it was proclaimed that AF shows bright greenish‐yellow fluorescence (BGYF) under ultraviolet (UV) light at a wavelength of 365 nm (Wicklow, 1999). Soemantri and Diyono (2019) applied this information for rapid detection of AF in corn using UV sensing digital camera with 5‐watt UV lamps. They built ANN architecture considering 10 input parameters, viz.…”
Section: Application Of Digital Color Imaging For Mold and Mycotoxins...mentioning
confidence: 99%
“…Their results showed the highest accuracy of 96.35% for nuts over other samples tested (corn) [200,201]. Soemantri et al reported even higher accuracy for corn (an average accuracy of 99%) [202].…”
Section: Image Processingmentioning
confidence: 89%